BRIDGING THE GAP: CRITICAL ANALYSIS OF WOMEN’S RIGHT UNDER INDIA’S NEW LABOUR CODES - Dr Smt Ashwini V Kulkarni (International Educational Journal of Science and Engineering, 2025)
The Indian labour laws being codified under four comprehensive Labour Codes represent the biggest change in the Indian employment and IR regime. One of the aims of the labour law modifications is the advancement of gender equality and better women’s rights in the working environment. In this context, the article critically analyses whether the new Labour Codes successfully fill the gaps in the women’s rights in the working environment or simply rehash previous efforts without confronting the intrinsic inequalities. By carrying out a scholarly and analytic assessment of the Code on Wages, 2019; Industrial Relations Code, 2020; Code on Social Security, 2020; Code on Social Security; and the Occupational Safety, Health and Working Conditions Code, 2020, the article critically analyses the central issues of equal remuneration for women; maternity security; night work; social security schemes for women; and occupational security. The paper indicates the progressive aspects of the new Labour Codes in the Indian context that stipulate the broadening of the labour law coverage and employment flexibility opportunities for women. Further, the article discusses the major issues with the new Labour Codes that diminish the enforcement of the labour laws in the Indian context; failure to provide social security coverage for the informal sector; failure to provide social security coverage for the gig sector; and failure of the gender-inclusive labour law regimes. The article states that the new Labour Codes in the Indian context lack to achieve the gender equality of women in the working environment.